A novel method for diagnosis of smear-negative tuberculosis patients by combining a random unbiased Phi29 amplification with a specific real-time PCR. Issue 4 (July 2015) - Pang, Yu; Lu, Jie; Yang, Jian; Wang, Yufeng; Cohen, Chad; Ni, Xin; Zhao, Yanlin
Summary In this study, we develop a novel method for diagnosis of smear-negative tuberculosis patients by performing a random unbiased Phi29 amplification prior to the use of a specific real-time PCR. The limit of detection (LOD) of the conventional real-time PCR was 100 colony-forming units (CFU) of MTB genome/reaction, while the REPLI real-time PCR assay could detect 0.4 CFU/reaction. In comparison with the conventional real-time PCR, REPLI real-time PCR shows better sensitivity for the detection of smear-negative tuberculosis (P = 0.015).